Cross-Border Issues in Collective Management - Moscoso, Adriana (The Columbia Journal of Law & the Arts, 2011)
I was an LLM student here a few years ago, so I am very happy to be back here today. I want to thank Professor Ginsburg for giving me this opportunity and I also want to thank the team from the Kernochan Center for its support. They have invited me to come and talk about cross-border licensing issues in Europe. I do not know how familiar everyone is with all of the things that have been going on in the last ten years in Europe concerning this issue. So, I am going to go through the steps that we have undertaken. At the end, I would like to share with you my ideas about what the future of collective management for online works should be, in Europe and worldwide. No article PDF is available.